2016
DOI: 10.1080/21505594.2016.1250994
|View full text |Cite
|
Sign up to set email alerts
|

RNAseq reveals hypervirulence-specific host responses toM. tuberculosisinfection

Abstract: The distinguishing factors that characterize the host response to infection with virulent Mycobacterium tuberculosis (M.tb) are largely confounding. We present an infection study with 2 genetically closely related M.tb strains that have vastly different pathogenic characteristics. The early host response to infection with these detergent-free cultured strains was analyzed through RNAseq in an attempt to provide information on the subtleties which may ultimately contribute to the virulent phenotype. Murine bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…4A). Interestingly the majority of these genes were also expressed by macrophages upon infection with a hypervirulent Mtb strain (30, 31). The top 20 genes with the highest p values were shown with the heat map demonstrated that SAA3 is one of the most highly upregulated genes by ESAT-6 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4A). Interestingly the majority of these genes were also expressed by macrophages upon infection with a hypervirulent Mtb strain (30, 31). The top 20 genes with the highest p values were shown with the heat map demonstrated that SAA3 is one of the most highly upregulated genes by ESAT-6 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Its upregulation has also been observed in response to a number of Gram-positive and Gram –negative, and acid-fast bacteria from as early as 4 h p.i. These pathogens include Brucella abortus [9], Chlamydia trachomatis [6], Lactobacillus acidophilus [10], Chlamydia pneumoniae [7], Listeria monocytogenes [8], Mycobacterium leprae [13] and in Mycobacterium tuberculosis [11] (a previous study in our lab). Questions regarding the biological role of OASL during M. tuberculosis infection remained unanswered.…”
Section: Discussionmentioning
confidence: 99%
“…One of the modalities by which macrophages sense and respond to Mtb is by changing transcription 4,5 , which leads to an increased pro-inflammatory state 4,6 . However, many other cellular processes (e.g.…”
Section: Introductionmentioning
confidence: 99%